Pengaruh Environmental, Social, and Governance (ESG) terhadap Financial Performance : Peran Struktur Kepemilikan sebagai Variabel Pemoderasi - Hidayatul Aisyah Nur Rohman; Nur Ainiyah; M.Bahril Ilmidaviq (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This study aims to examine the impact of each ESG (environmental, social, governance) aspect on the financial performance of mining companies listed on the Indonesia Stock Exchange, with ownership structure proxied by managerial ownership as a moderating variable. This quantitative research employs purposive sampling, resulting in a sample of 10 mining companies listed on the IDX for the period 2019-2023. Data analysis was conducted using SPSS version 22 with multiple linear regression and Moderate Regression Analysis (MRA) methods. The results show that both partially and simultaneously, all ESG variables affect financial performance, though the social aspect has a negative impact. Additionally, managerial ownership is proven to moderate the relationship between ESG aspects and financial performance.